Hercules : the man, the myth, the hero - Lasky, Kathryn (Hyperion Books for Children, 1997)
Recounts the story of the mythological hero, Hercules, child of Zeus and a mortal woman, including his twelve labors and ending with his ascension to Mount Olympus as a god.